Introduction of Hiragana and Katakana Letters Learning Media Using Voice Command Method to Improve Japanese Language Learning Ability Based on Augmented Reality - Abrilia Agnisa Putri; Muhamad Azrino Gustalika (Telkom University, 2025)
The purpose of this study is to use the MDLC technique to create and develop interactive learning materials for the letters Hiragana and Katakana using Augmented Reality (AR) on Android devices. XI grade students participated in this study, which was conducted at SMA Negeri 1 Ajibarang. The stages in the Multimedia Development Life Cycle (MDLC) - conceptualization, design, materials collection, assembly, testing, and distribution - were followed when developing the application. Users can easily navigate and interact with this application by using voice commands thanks to the Voice Command functionality. A Black Box Testing approach was used for functionality testing, which showed that all features of the app functioned as intended without any issues. Furthermore, the System Usability Scale (SUS) feasibility test had an average value of 82.67%, falling into the “B” category with a feasibility level of “Good” which users found acceptable. This AR application presents an interactive 3D visualization of Japanese letters, making it easier for students to understand the material and increase motivation and engagement in learning. Recommendations for future development include expanding the application to other materials, adding new features to enrich the learning experience, training teachers for optimal use of the application, and periodic evaluation based on user feedback.